Metal surface treatment liquid and its application and application method

By using fluorine-free metal surface treatment liquid, including polyacid, titanium oxidation regulator and organic acid additive, combined with anodizing and cleaning liquid treatment, the environmental and corrosion problems caused by the use of fluorine ions in the prior art are solved, and the effective fluorine-free treatment and nanopore formation of the surface of titanium-aluminum composite parts are achieved, and the bonding strength between metal and resin is improved.

CN119736688APending Publication Date: 2025-04-01DONGGUAN HUIZELING CHEM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411943029.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art uses fluorine ions when treating titanium-aluminum composites, resulting in unfriendly environment and excessive corrosion to the metal surface, making it difficult to effectively treat fluorine-free surfaces.

Method used

A fluorine-free metal surface treatment liquid is used to form nanopores by anodizing treatment, combined with alkaline or neutral cleaning liquid to protect the metal surface.

Benefits of technology

The surface of titanium-aluminum composites is achieved without fluorine, forming a nanopore structure, improving the bonding strength between metal and resin, and being more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736688A_ABST
    Figure CN119736688A_ABST
Patent Text Reader

Abstract

The present invention provides a metal surface treatment liquid and its application and application method, the metal surface treatment liquid comprises a polyacid, a titanium oxide regulator and an organic acid additive, wherein the mass content of the polyacid accounts for A in the total mass of the metal surface treatment liquid, the mass content of the titanium oxide regulator accounts for B in the total mass of the metal surface treatment liquid, the mass content of the organic acid additive accounts for C in the total mass of the metal surface treatment liquid, and the three of A, B and C satisfy the relationship: 10<B / C<1.5A, and A+B+C=100%. Compared with the prior art, the metal surface treatment liquid of the present invention does not contain fluoride ions, is more environmentally friendly, and the three components in the present invention are used in combination with a synergistic effect, can effectively perform surface treatment on the metal to generate nanopores on its surface and protect the metal from excessive dissolution, and improve the subsequent bonding strength between the metal parts and the resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of surface treatment technology, and specifically to a metal surface treatment liquid and its application and application method. Background Art

[0002] In the fields of mobile communication equipment, electronic and electrical equipment, automobile machinery, etc., in order to achieve the purpose of reducing product weight and increasing bonding strength, metal and resin integrated molding technology has been widely developed and fully applied. At present, many patents have emerged involving microporous injection molding integrated molding technology of various materials. The metal structure covers single metal and multi-metal composite parts. Among them, titanium aluminum composite parts have gradually been favored by developers for their excellent properties of both titanium alloy and aluminum alloy. However, in the field of surface treatment, the combination of two heterogeneous metals greatly increases the difficulty of surface treatment. Because the conductivity of each metal is different and there is a potential difference between the metals, when etching two metal materials at the same time, when one of the metals is pore-forming, the other metal will be severely corroded and its structure will be damaged, thereby causing the entire metal product to be destroyed.

[0003] To this end, developers have designed a one-step or multi-step etching process to produce micron or nanopores on the composite parts. For example, patents CN114606560A and CN117210905A use oxidation etching and other methods to make micron pores on the surface of titanium-aluminum composite parts. Patent CN117822085A uses a system of fluoride, solvent and acid to make nanopores on titanium-aluminum composite parts. There are also a large number of uses of fluorine-containing anodizing to make nano- or micron pores on the surface of titanium alloys. The composite parts are formed into metal and resin composites by injection molding.

[0004] However, the above-mentioned treatment methods all use fluorine or fluoride when treating titanium alloys, and the importance of fluorine-free titanium-aluminum composite surface treatment processes has become increasingly prominent. In view of this, it is indeed necessary to provide a fluorine-free metal surface treatment liquid and a fluorine-free surface treatment process for titanium-aluminum composite parts applied to the metal surface treatment liquid. Summary of the invention

[0005] One of the purposes of the present invention is to provide a metal surface treatment liquid to improve the problem that the existing metal surface treatment liquid is not environmentally friendly and excessively corrodes the metal surface.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A metal surface treatment liquid comprises a polyacid, a titanium oxide regulator, an organic acid additive and water, wherein the mass content of the polyacid accounts for A in the total mass of the metal surface treatment liquid, the mass content of the titanium oxide regulator accounts for B in the total mass of the metal surface treatment liquid, the mass content of the organic acid additive accounts for C in the total mass of the metal surface treatment liquid, and the remainder is water; A, B and C satisfy the relationship: 10<B / C<1.5A, and 31%≤A+B+C≤75%.

[0008] Preferably, the A is 10-30%, the B is 20-40%, and the C is 1-5%.

[0009] Preferably, the polyacid comprises at least one of sulfuric acid, phosphoric acid or periodic acid;

[0010] The titanium oxide regulator includes hydrogen peroxide and a hydrogen peroxide stabilizer, perchloric acid or its salt, a viscosity regulator and water;

[0011] The organic acid adjuvant includes at least one of oxalic acid, tartaric acid, lactic acid, citric acid, malic acid, succinic acid, boric acid, sulfosalicylic acid, aminoacetic acid and aminosulfonic acid.

[0012] Preferably, the hydrogen peroxide stabilizer includes one or more of hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, ethylenediaminetetramethylene phosphonic acid, diethylenetriaminepentamethylene phosphonic acid, polyethylenepolyaminopolymethylene phosphonic acid, hydroxypropylene diphosphonic acid, and tetramethylene phosphonic acid; the viscosity modifier includes at least one of a polyhydroxy compound or a polymer of a polyhydroxy compound.

[0013] Preferably, the mass content of hydrogen peroxide accounts for D of the mass of the titanium oxide adjuster, the mass content of the hydrogen peroxide stabilizer accounts for E of the mass of the titanium oxide adjuster, the mass content of the perchloric acid or its salt accounts for F of the mass of the titanium oxide adjuster, and the mass content of the viscosity regulator accounts for G of the mass of the titanium oxide adjuster, wherein D, E, F, and G satisfy the relationship: 1.5<(D+G) / (E+F)<6, and 30%<D+G+E+F<100%.

[0014] Preferably, the D is 10-30%, the E is 1-10%, the F is 10-20%, and the G is 10-30%.

[0015] A second object of the present invention is to provide an application of a metal surface treatment liquid, wherein the metal surface treatment liquid is applied to the surface treatment of a titanium-aluminum composite part, wherein the titanium-aluminum composite part is a composite part formed by solid-state bonding of a titanium alloy and an aluminum alloy metal matrix.

[0016] The third object of the present invention is to provide a method for applying a metal surface treatment liquid, comprising the following steps:

[0017] S1, pre-treating the titanium-aluminum composite member to expose the titanium-aluminum composite member substrate;

[0018] S2, placing the pre-treated titanium-aluminum composite substrate as an anode in a metal surface treatment solution, and simultaneously performing anodizing treatment on the titanium alloy and the aluminum alloy until a large number of holes are formed on the surfaces of the titanium alloy and the aluminum alloy;

[0019] S3. The anodized titanium-aluminum composite part is placed in an alkaline or neutral cleaning solution for immersion or ultrasonic treatment.

[0020] Preferably, the pre-treatment in S1 includes degreasing, activating and deashing the titanium-aluminum composite part.

[0021] Preferably, the voltage of the S2 anodizing treatment is 10V-50V, the time of the anodizing treatment is 10min-30min, the temperature of the anodizing treatment is 15°C-45°C, and the pore size of the pores is 10nm-60nm.

[0022] Compared with the prior art, the beneficial effects of the present invention are: the metal surface treatment liquid of the present invention does not contain fluoride ions, is more environmentally friendly, and the three components of the present invention are used in combination with a synergistic effect, which can effectively perform surface treatment on the metal to produce nanopores on its surface and protect the metal from excessive dissolution, thereby improving the subsequent bonding strength between metal parts and resins. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a picture of the titanium alloy portion on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 150K magnification after the titanium-aluminum composite part was treated in Example 1 before injection molding;

[0024] Figure 2 This is a picture of the aluminum alloy portion of the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 150K magnification after the titanium-aluminum composite part was treated and before injection molding in Example 1;

[0025] Figure 3 This is a picture of the titanium alloy part on the titanium-aluminum composite part after the titanium-aluminum composite part is treated in Comparative Example 1 and before injection molding, observed by SU-70 thermal field emission scanning electron microscope at a magnification of 200K times;

[0026] Figure 4 This is a picture of the aluminum alloy part on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 200K magnification after the titanium-aluminum composite part was treated in comparative example 1 before injection molding;

[0027] Figure 5 This is a picture of the titanium alloy portion on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 200K magnification after the titanium-aluminum composite part was treated in Comparative Example 2 before injection molding;

[0028] Figure 6 This is a picture of the aluminum alloy part on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 150K times after the titanium-aluminum composite part was treated in comparative example 2 before injection molding;

[0029] Figure 7 This is a picture of the titanium alloy portion on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 150K times after the titanium-aluminum composite part was treated in Comparative Example 3 before injection molding;

[0030] Figure 8 This is a picture of the aluminum alloy portion on the titanium-aluminum composite part observed by SU-70 thermal field emission scanning electron microscope at 150K magnification after the titanium-aluminum composite part was treated in Example 3 but before injection molding. DETAILED DESCRIPTION

[0031] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0032] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0033] According to the first aspect of the present application, the present application provides a metal surface treatment liquid, including a polyacid, a titanium oxide regulator, an organic acid additive and water, wherein the mass content of the polyacid accounts for A of the total mass of the metal surface treatment liquid, the mass content of the titanium oxide regulator accounts for B of the total mass of the metal surface treatment liquid, the mass content of the organic acid additive accounts for C of the total mass of the metal surface treatment liquid, and the remainder is water; the three of A, B, and C satisfy the relationship: 10<B / C<1.5A, and 31%≤A+B+C≤75%.

[0034] In the present invention, the polyacid mainly plays a role in forming a film on the metal surface under the action of electricity. Based on the well-known anodic oxidation film formation and film dissolution theory, when the metal surface is subjected to constant voltage anodic oxidation, a dense oxide film will quickly form on the titanium and aluminum surfaces at the initial stage of electricity, the surface resistance will increase, and the current will decrease. As the oxidation proceeds, a nanoporous layer with controllable pore size and pore depth can be formed on the metal surface, which can significantly improve the subsequent bonding strength with the resin.

[0035] In some embodiments, the A is 10-30%, the B is 20-40%, and the C is 1-5%.

[0036] In some embodiments, the polyacid includes at least one of sulfuric acid and phosphoric acid; phosphoric acid becomes the first acid used as an oxidizing acid to improve the bonding strength with the attached object due to its large pore size and special oxide film properties.

[0037] The titanium oxide regulator includes hydrogen peroxide and a hydrogen peroxide stabilizer, perchloric acid or its salt, a viscosity regulator and water;

[0038] The organic acid adjuvant includes at least one of oxalic acid, tartaric acid, lactic acid, citric acid, malic acid, succinic acid, boric acid, sulfosalicylic acid, aminoacetic acid and aminosulfonic acid.

[0039] In some embodiments, the hydrogen peroxide stabilizer includes one or more of hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, ethylenediaminetetramethylene phosphonic acid, diethylenetriaminepentamethylene phosphonic acid, polyethylenepolyaminopolymethylene phosphonic acid, hydroxypropylene diphosphonic acid, and tetramethylene phosphonic acid; the viscosity modifier includes at least one of a polyhydroxy compound or a polymer of a polyhydroxy compound.

[0040] Preferably, the mass content of hydrogen peroxide accounts for D of the mass of the titanium oxide adjuster, the mass content of the hydrogen peroxide stabilizer accounts for E of the mass of the titanium oxide adjuster, the mass content of the perchloric acid or its salt accounts for F of the mass of the titanium oxide adjuster, and the mass content of the viscosity regulator accounts for G of the mass of the titanium oxide adjuster, wherein D, E, F, and G satisfy the relationship: 1.5<(D+G) / (E+F)<6, and 30%<D+G+E+F<100%.

[0041] Among them, hydrogen peroxide in the titanium oxidant is an excellent complexing agent and oxygen free radical releaser for titanium ions. Anodic oxidation is a very complex electrochemical reaction process. Its mechanism cannot be explained by a single chemical reaction formula and a unified chemical theory. However, it can be basically understood that in the early stage of oxidation, titanium atoms lose electrons and become titanium ions. When power is applied, the oxygen free radicals generated at the anode combine with titanium ions to form titanium oxides such as titanium dioxide. Like fluoride ions, under strong acid conditions, hydrogen peroxide will form stable colored mononuclear ions {[Ti(O2)OH(H2O)4] +}, which can significantly reduce the titanium ions that generate the titanium oxide film, greatly promoting the film dissolution rate. In addition, the instability of hydrogen peroxide is that it will release nascent oxygen and decompose into oxygen and water. According to the oxide film formation theory "oxygen bubble method", in the early stage of oxide film formation, oxygen will first be adsorbed at the generation site and gradually increase, then desorbed, and finally overflow from the pores. The size of the oxygen bubble and the overflow path will affect the pore size and thickness of the porous layer of the oxide film. The present invention promotes the generation of oxygen by adding hydrogen peroxide, thereby promoting the growth and thickening of the titanium porous film layer.

[0042] The hydrogen peroxide stabilizer can effectively complex other metal ions precipitated from the surface of the dissolved metal, such as vanadium in titanium alloy, zinc and copper in aluminum alloy, to prevent the decomposition of hydrogen peroxide, maintain the oxidation capacity of the metal surface treatment liquid reaction, and extend the life of the liquid; on the other hand, it can also coordinate with hydrogen peroxide to form a water-soluble peroxide complex {[TiO(H2O2) X ] 2-}, effectively promote the dissolution of Ti and promote film formation and dissolution effect.

[0043] Perchloric acid or its salts mainly act on perchlorate, preferably perchloric acid, sodium perchlorate or ammonium perchlorate, which mainly breaks the titanium oxide film through the strong oxidizing property of perchlorate. According to the theory of perchlorate electrochemical polishing under acidic conditions, when perchlorate reaches a certain concentration, ablated point-shaped oxide film will appear on the surface of the titanium alloy, that is, polarization points are generated on the dense titanium dioxide oxide film, and the oxide film point-shaped pore formation "Matthew effect" is generated under the action of hydrogen peroxide. The "Matthew effect" is that when a point corrosion is formed, all the current will be concentrated here, causing this point to be corroded more severely, and other positions are weakly corroded because the current is sucked away, thereby promoting the formation of porous oxide film on the metal surface.

[0044] The viscosity regulator plays a major role in regulating the current in metal anodizing. For example, when conventional inorganic acids are used to oxidize aluminum materials, at a constant voltage, the current slowly decreases in the subsequent stable stage. However, since a large amount of hydrogen peroxide and perchlorate are introduced into the oxidation system, the electrolyte strength in the solution is significantly increased, the bath liquid resistance is reduced, and the stable current is significantly larger than the conventional current. In order to reduce the problem of ablation and powdering of the oxide film on aluminum caused by excessive current, the present invention introduces polyhydroxy compounds or polymers of polyhydroxy compounds. First, the stable current is reduced from the perspective of the electrolyte. Second, the polyhydroxy compound itself is a wide-temperature additive and corrosion inhibitor for aluminum anodizing. The two together produce a synergistic effect on improving the performance of the aluminum oxide film.

[0045] Preferably, the D is 10-30%, the E is 1-10%, the F is 10-20%, and the G is 10-30%.

[0046] The organic acid additive described in the present invention mainly plays a role in modifying the performance of the oxide film. As mentioned above, when the acidic perchlorate reaches a certain concentration, it will produce pitting ablation on the metal surface. The purpose of the present invention is to generate nanopores on the metal surface. Similarly, the acidic perchlorate will also produce pitting ablation on the metal surface, destroying the porous film generated by the original phosphoric acid. The organic acid can release H +, adjust the acidic environment. As it is a weak acid with weak conductivity and dissolving ability, it can regulate the dissolution of the metal surface during the electrolysis process, which is beneficial to inhibit the strong oxidizing property of perchlorate, which causes the pore wall to dissolve and destroy the pore structure. However, organic acid has a weak effect on the formation of titanium oxide film and will not form a rich phase in the metal. Therefore, organic acid has little effect on the titanium alloy part when inhibiting perchlorate ablation. In addition, according to public information, adding an appropriate amount of organic acid to the inorganic acid oxidizing solution will significantly improve the corrosion resistance of the oxide film, especially for aluminum alloy oxide film.

[0047] According to a second aspect of the present application, the present application provides an application of a metal surface treatment liquid, wherein the metal surface treatment liquid is applied to the surface treatment of a titanium-aluminum composite part, wherein the titanium-aluminum composite part is a composite part formed by solid-state bonding of a titanium alloy and an aluminum alloy metal matrix.

[0048] According to a third aspect of the present application, the present application provides a method for applying a metal surface treatment liquid, comprising the following steps:

[0049] S1, pre-treating the titanium-aluminum composite member to expose the titanium-aluminum composite member substrate;

[0050] S2, placing the pre-treated titanium-aluminum composite substrate as an anode in a metal surface treatment solution, and simultaneously performing anodizing treatment on the titanium alloy and the aluminum alloy until a large number of holes are formed on the surfaces of the titanium alloy and the aluminum alloy;

[0051] S3. The anodized titanium-aluminum composite part is placed in an alkaline or neutral cleaning solution for immersion or ultrasonic treatment.

[0052] In the embodiment of the present invention, the pretreatment in step S1 includes degreasing, activating and deashing the titanium-aluminum composite. The titanium-aluminum composite is degreased to remove oil stains on the surface of the titanium-aluminum composite; the titanium-aluminum composite is activated, usually with a high concentration of sulfuric acid and corrosion inhibitor additives, mainly to activate and remove the titanium natural oxide film and aluminum natural oxide on the titanium-aluminum composite at the same time; the titanium-aluminum composite is deashed, which mainly removes the floating ash remaining when activating and removing the oxide film, and a conventional acidic deashing agent is usually sufficient.

[0053] In step S3, the main purpose is to remove the residual acid and anion in the nanopores of the titanium-aluminum composite to prevent the subsequent residual reagents from damaging the titanium-aluminum nanopores; in addition, a very thin adsorption filling film is adsorbed on the nanopores of the titanium-aluminum composite. This filling film can undergo a condensation reaction with the hydroxyl groups on the surface of the plastic reinforcement glass fiber material to generate stable silicon-oxygen bonds, which can not only protect the surface activity of the bonding layer, but also undergo a cross-linking reaction with the hot flow plastic during injection molding, thereby greatly increasing the bonding strength between the titanium-aluminum composite and the resin.

[0054] In the embodiment of the present invention, the voltage of the S2 anodizing treatment is 10V-50V, the time of the anodizing treatment is 10min-30min, the temperature of the anodizing treatment is 15°C-45°C, and the pore size of the pores is 10nm-60nm.

[0055] The metal surface treatment liquid provided by the present invention can etch titanium alloy and aluminum alloy at the same time and form nanoscale holes of similar size and uniformity, with a certain depth and density on the surfaces of the two materials. The formed nanoscale holes are suitable for high-strength engineering resin nano-injection molding. During injection molding, the molten resin enters the nanopores, and the resin and the nanopores on the surface of the titanium-aluminum composite form an interactively embedded anchor structure, thereby obtaining a titanium-aluminum composite and resin combination with high-strength bonding.

[0056] It should be noted that the titanium-aluminum composite part in the present invention is a composite part formed by solid-state bonding of titanium alloy and aluminum alloy metal matrix, rather than the so-called alloy in the metallurgical field, and the two are non-homogeneous phase metals. Specifically, it can be understood as a composite part formed by bonding a single titanium alloy metal and a single aluminum alloy metal together after treatment, wherein the bonding method includes composite parts made by explosion welding, electromagnetic continuous casting, casting, hot melt pressing, diffusion welding, ultrasonic welding, casting composite method, rolling, liquid-solid phase casting and rolling, etc. In addition, composite parts composed of titanium alloy and aluminum alloy by riveting, bundling, pressing, etc. also belong to the definition of composite parts described in the present invention.

[0057] The present invention will be further described below with reference to specific embodiments and comparative examples.

[0058] Example 1

[0059] One of the application methods of the metal treatment liquid in the present invention comprises the following steps:

[0060] S1: First, place the titanium-aluminum composite product (titanium and aluminum each occupy 1 / 2 of the surface area, and the end is the injection point) in a special cleaning agent for titanium-aluminum composite parts, CW-6007 (produced by Dongguan Huizeling Chemical Technology Co., Ltd.), and wash it for 5-10 minutes, then rinse it thoroughly with water. The cleaning temperature is 40-60℃, and ultrasonic cleaning is used as an auxiliary.

[0061] Then, the titanium aluminum composite parts after degreasing and cleaning are immersed in 20% sulfuric acid and 20% activation additive HLD-060E (produced by Dongguan Huizeling Chemical Technology Co., Ltd.) for 2-5 minutes to remove the oxide film on the surface of the titanium aluminum composite parts, and then washed with water, and the temperature is set to 75-85°C.

[0062] Then immerse the activated titanium-aluminum composite parts in 10% sulfuric acid and 10% ammonia-free nitrogen deashing agent CWF-6024 (produced by Dongguan Huizeling Chemical Technology Co., Ltd.) for 2-5 minutes to remove the black ash produced by the surface of the oxide film, and then wash them with water. The temperature is set to 30-40°C. Commercially available special deashing agents or nitric acid can also be used instead of the above-mentioned ammonia-free nitrogen deashing agent.

[0063] S2: The pre-treated titanium-aluminum composite part is placed in a metal treatment solution composed of 15wt% phosphoric acid, 30wt% titanium oxide regulator, and 3wt% organic acid auxiliary agent and water for anodization for 20 minutes and then washed with water.

[0064] The oxidation voltage is 16V, the temperature is set to 20°C; the titanium oxidation regulator is composed of 20% hydrogen peroxide, 15% sodium perchlorate, 5% hydroxyethylidene diphosphonic acid, 15% propylene glycol and water, and the organic acid auxiliary is lactic acid.

[0065] S3: The anodized titanium-aluminum composite part is placed in 3% triethanolamine, 3% 3-aminopropyltrimethoxysilane and water and soaked for 5 minutes, then washed with water, and the temperature is set to room temperature.

[0066] S4: The cleaned titanium-aluminum composite part is placed in a clean oven for drying to remove surface moisture, thereby completing the surface treatment of the titanium-aluminum composite part.

[0067] The titanium-aluminum composite parts treated as above are combined with plastics by injection molding to obtain titanium-aluminum composite parts and plastic parts combined test samples. The plastic used for this verification is Tosoh's PPS, model SGX-120.

[0068] Example 2

[0069] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 10% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 20% hydrogen peroxide, 15% sodium perchlorate, 5% hydroxyethylidene diphosphonic acid, 15% propylene glycol and water, and the organic acid additive is lactic acid.

[0070] The rest is the same as in Example 1 and will not be described again here.

[0071] Example 3

[0072] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 30% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 20% hydrogen peroxide, 15% sodium perchlorate, 5% hydroxyethylidene diphosphonic acid, 15% propylene glycol and water, and the organic acid additive is lactic acid.

[0073] The rest is the same as in Example 1 and will not be described again here.

[0074] Example 4

[0075] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 15% hydrogen peroxide, 10% perchloric acid, 5% hydroxyethylidene diphosphonic acid, 15% propylene glycol and water, and the organic acid additive is lactic acid.

[0076] The rest is the same as in Example 1 and will not be described again here.

[0077] Example 5

[0078] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 15% hydrogen peroxide, 15% sodium perchlorate, 10% tetramethylenephosphonic acid, 15% propylene glycol and water, and the organic acid additive is lactic acid.

[0079] The rest is the same as in Example 1 and will not be described again here.

[0080] Example 6

[0081] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 15% hydrogen peroxide, 15% sodium perchlorate, 10% tetramethylenephosphonic acid, 10% propylene glycol and water, and the organic acid additive is lactic acid.

[0082] The rest is the same as in Example 1 and will not be described again here.

[0083] Example 7

[0084] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster, 5% organic acid additive and water, wherein the titanium oxide adjuster is composed of 15% hydrogen peroxide, 15% sodium perchlorate, 10% tetramethylenephosphonic acid, 15% propylene glycol and water, and the organic acid additive is sulfosalicylic acid.

[0085] The rest is the same as in Example 1 and will not be described again here.

[0086] Example 8

[0087] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 15% phosphoric acid, 20% titanium oxide adjuster, 3% organic acid additive and water, wherein the titanium oxide adjuster is composed of 20% hydrogen peroxide, 20% sodium perchlorate, 15% diethylenetriamine penta (methylene phosphonic acid), 10% diethylene glycol and water, and the organic acid additive is malic acid.

[0088] The rest is the same as in Example 1 and will not be described again here.

[0089] Example 9

[0090] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 20% phosphoric acid, 20% titanium oxide adjuster, 1% organic acid additive and water, wherein the titanium oxide adjuster is composed of 10% hydrogen peroxide, 10% perchloric acid, 10% aminotri(methylene)phosphoric acid, 15% decaglycerol and water, and the organic acid additive is oxalic acid.

[0091] The rest is the same as in Example 1 and will not be described again here.

[0092] Example 10

[0093] The difference from Example 1 is that the metal surface treatment liquid in step S2 of this embodiment is adjusted to 25% phosphoric acid, 25% titanium oxide adjuster, 5% organic acid additive and water, wherein the titanium oxide adjuster is composed of 20% hydrogen peroxide, 20% sodium perchlorate, 15% diethylenetriamine penta (methylene phosphonic acid), 10% diethylene glycol and water, and the organic acid additive is malic acid.

[0094] The rest is the same as in Example 1 and will not be described again here.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that the metal surface treatment liquid in step S2 is adjusted to 15% phosphoric acid, 3% organic acid additive and water, without adding titanium oxide adjuster, and the organic acid additive is lactic acid.

[0097] The rest is the same as in Example 1 and will not be described again here.

[0098] Comparative Example 2,

[0099] The difference from Example 1 is that the metal surface treatment liquid in step S2 is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster, 3% organic acid auxiliary agent and water, the organic acid auxiliary agent is lactic acid, but no perchloric acid or perchlorate is added to the titanium oxide adjuster.

[0100] The rest is the same as in Example 1 and will not be described again here.

[0101] Comparative Example 3

[0102] The difference from Example 1 is that the metal surface treatment solution in step S2 is adjusted to 15% phosphoric acid, 30% titanium oxide adjuster and water, that is, no organic acid additive is added.

[0103] The rest is the same as in Example 1 and will not be described again here.

[0104] The surfaces of the aluminum-titanium composite parts obtained in the above-mentioned embodiments and comparative examples were observed by using a SU-70 thermal field emission scanning electron microscope, as shown in the attached drawings.

[0105] Tensile tests were performed on the embodiments and comparative examples to examine the bonding strength between the titanium-aluminum composite material and the plastic part, and the test results are recorded in Table 1 below.

[0106] The specific method of the tensile test is as follows: the embodiment and the comparative example are clamped on the tensile tester fixture, the pull head and the fixture make relative movement, the maximum tensile value when the titanium-aluminum composite part and the plastic are broken by the tester, and then converted into MPa according to the actual bonding contact area between the titanium-aluminum composite part and the plastic.

[0107] The product in the test sample used is a titanium-aluminum composite material with an end face size of 12mm*30mm (titanium and aluminum each account for 50% of the surface area), and the end face of the product is combined with the plastic part after injection molding.

[0108] Table 1

[0109] Group Tensile force Example 1 40.5Mpa Example 2 40.7Mpa Example 3 40.9Mpa Example 4 41.2Mpa Example 5 41.0Mpa Example 6 40.1Mpa Example 7 40.4Mpa Example 8 41.3Mpa Example 9 41.5Mpa Example 10 40.9Mpa Comparative Example 1 18.8Mpa Comparative Example 2 24.6Mpa Comparative Example 3 26.8Mpa

[0110] pass Figures 1 to 8 It can be seen from the SEM morphology photography and the results listed in Table 1 that the titanium-aluminum composite parts treated with the fluorine-free metal surface treatment liquid of the present invention can significantly improve the bonding strength between the titanium-aluminum composite parts and the plastic after injection molding and plastic bonding.

[0111] Figure 1 and Figure 2 As shown, it can be seen from the SEM morphology that a large number of 10nm-60nm nano-scale pores are distributed on the titanium alloy part of the titanium-aluminum composite, and 10nm-60nm nano-scale pores are distributed on the aluminum alloy part of the titanium-aluminum composite.

[0112] Figure 3 and Figure 4 As shown, it can be seen from the SEM morphology that the titanium-aluminum composite part without titanium oxide regulator has no dense oxide film on the titanium alloy part of the titanium-aluminum composite, no obvious effective nanopores, and cannot be used for nano injection molding. However, due to the presence of phosphoric acid and organic acid, the aluminum alloy part of the titanium-aluminum composite part is still distributed with 10nm-60nm nanoscale holes. During injection molding, the titanium-aluminum composite parts are injected at the same time, that is, the end of the test piece is divided into half with residual glue and half without residual glue, and the tensile value is only half of the tensile value of Example 1.

[0113] Figure 5 and Figure 6 As shown, it can be seen from the SEM morphology that the titanium-aluminum composite made without adding perchloric acid or perchlorate titanium oxide regulator has a slight nanopore morphology on the titanium alloy part of the titanium-aluminum composite, the pore ratio is low and the pore diameter of the nanopore is very small, and the nano injection molding effect is poor. Due to the presence of phosphoric acid and organic acid, the aluminum alloy part of the titanium-aluminum composite is still distributed with 10nm-60nm nanoscale holes. During injection molding, the titanium-aluminum composite is injected at the same time, that is, the end of the test piece is divided into half with residual glue and half with poor residual glue, and the tensile value is lower than the tensile value of Example 1.

[0114] Figure 7 and Figure 8 As shown, it can be seen from the SEM morphology that the titanium-aluminum composite made without adding organic acid additives has 10-60nm nano-scale distributed on the titanium alloy part of the titanium-aluminum composite, and although the aluminum alloy part of the titanium-aluminum composite is also distributed with nanopores, it can be seen from the SEM morphology that the nanopores are obviously collapsed and over-etched. During injection molding, the titanium-aluminum composite is injected at the same time, that is, the end of the test piece is divided into half with residual glue and half with poor residual glue, and the tensile value is lower than the tensile value of Example 1.

[0115] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A metal surface treatment liquid, characterized in that: It includes a polyacid, a titanium oxide regulator, an organic acid additive and water, wherein the mass content of the polyacid accounts for A in the total mass of the metal surface treatment liquid, the mass content of the titanium oxide regulator accounts for B in the total mass of the metal surface treatment liquid, the mass content of the organic acid additive accounts for C in the total mass of the metal surface treatment liquid, and the rest is water; the three of A, B and C satisfy the relationship: 10<B / C<1.5A, and 31%≤A+B+C≤75%.

2. A metal surface treatment liquid according to claim 1, characterized in that: The A is 10-30%, the B is 20-40%, and the C is 1-5%.

3. A metal surface treatment liquid according to claim 1, characterized in that: The polyacid includes at least one of sulfuric acid and phosphoric acid; The titanium oxide regulator includes hydrogen peroxide and a hydrogen peroxide stabilizer, perchloric acid or its salt, a viscosity regulator and water; The organic acid adjuvant includes at least one of oxalic acid, tartaric acid, lactic acid, citric acid, malic acid, succinic acid, boric acid, sulfosalicylic acid, aminoacetic acid and aminosulfonic acid.

4. A metal surface treatment liquid according to claim 3, characterized in that: The hydrogen peroxide stabilizer includes one or more of hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid, ethylenediaminetetramethylene phosphonic acid, diethylenetriaminepentamethylene phosphonic acid, polyethylenepolyaminopolymethylene phosphonic acid, hydroxypropylene diphosphonic acid, and tetramethylene phosphonic acid; the viscosity modifier includes at least one of a polyhydroxy compound and a polymer of a polyhydroxy compound.

5. A metal surface treatment liquid according to claim 4, characterized in that: The mass content of hydrogen peroxide accounts for D of the mass of the titanium oxide adjuster, the mass content of the hydrogen peroxide stabilizer accounts for E of the mass of the titanium oxide adjuster, the mass content of the perchloric acid or its salt accounts for F of the mass of the titanium oxide adjuster, and the mass content of the viscosity modifier accounts for G of the mass of the titanium oxide adjuster, wherein D, E, F, and G satisfy the relationship: 1.5<(D+G) / (E+F)<6, and 30%<D+G+E+F<100%.

6. A metal surface treatment liquid according to claim 5, characterized in that: The D is 10-30%, the E is 1-10%, the F is 10-20%, and the G is 10-30%.

7. Use of a metal surface treatment liquid according to any one of claims 1 to 6, characterized in that: The metal surface treatment liquid is used for surface treatment of a titanium-aluminum composite part, wherein the titanium-aluminum composite part is a composite part formed by solid-state bonding of a titanium alloy and an aluminum alloy metal matrix.

8. The method for applying a metal surface treatment liquid according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, pre-treating the titanium-aluminum composite member to expose the titanium-aluminum composite member substrate; S2, placing the pre-treated titanium-aluminum composite substrate as an anode in a metal surface treatment solution, and simultaneously performing anodizing treatment on the titanium alloy and the aluminum alloy until a large number of holes are formed on the surfaces of the titanium alloy and the aluminum alloy; S3. The anodized titanium-aluminum composite part is placed in an alkaline or neutral cleaning solution for immersion or ultrasonic treatment.

9. The method for applying a metal surface treatment liquid according to claim 8, characterized in that: The pre-treatment in S1 includes degreasing, activating and deashing the titanium-aluminum composite part.

10. The method for applying a metal surface treatment liquid according to claim 8, characterized in that: The voltage of the S2 anodizing treatment is 10V-50V, the time of the anodizing treatment is 10min-30min, the temperature of the anodizing treatment is 15°C-45°C, and the pore diameter of the pores is 10nm-60nm.

Citation Information

Patent Citations

  • One-time etching method of titanium-aluminum composite part and preparation method of titanium-aluminum composite part and resin combination body

    CN117210905A

  • Electrolyte for surface treatment and surface treatment process of titanium-aluminum composite material

    CN117822085A